The relationship of students' satisfaction and academic performance: a case study for PR degree students UiTM Alor Gajah Melaka / Mohd Khairornizam Mohd Yunus and Abdul Rauf Ridzuan - Mohd Yunus, Mohd Khairornizam; Ridzuan, Abdul Rauf (Faculty of Communication & Media Studies, 2019)
A study of degree PR student's satisfaction about UiTM Alor Gajah, Melaka facilities here was commissioned by a comprehensive university to provide a professional evaluation of student. Such a study had not been completed in the past and was needed to align student services with the mission, long-range goals, and strategic planning of the university. The researcher conducted a survey and distributed 94 respondents in UiTM Melaka which consist of PR degree students. The study demonstrated that relationship among UiTM staff as significant factor that effect on the student's academic performance. Result of the research were analyzed and discussed regarding the relationship between satisfaction and academic performance. In this study, the researcher using assimilation theory to describe satisfaction for PR degree students' and the finding from this research showed that satisfaction among UiTM staff being is most significant factor among the three factors.